1996
DOI: 10.1021/ma9602233
|View full text |Cite
|
Sign up to set email alerts
|

Soluble, Rigid-Rod Polyamide, Polyimides, and Polyazomethine with Phenyl Pendent Groups Derived from 4,4‘‘-Diamino-3,5,3‘‘,5‘‘-tetraphenyl-p-terphenyl

Abstract: The reaction of 4,4‘-(1,4-phenylene)bis(2,6-diphenylpyrylium tetrafluoroborate) with nitromethane afforded 4,4‘‘-dinitro-3,5,3‘‘,5‘‘-tetraphenyl-p-terphenyl, which was catalytically hydrogenated to the corresponding diamine. The latter was used as starting material for the preparation of new rigid-rod polyamide, polyimides, and polyazomethine bearing phenyl pendent groups as well as the respective model compounds. Characterization of polymers was accomplished by inherent viscosity measurements, elemental analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
59
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 100 publications
(59 citation statements)
references
References 26 publications
0
59
0
Order By: Relevance
“…[6][7][8] Significant synthetic efforts in the area of high-performance polymers have been focused on improving the processability and solubility of PIs through the design and synthesis of new monomers. Various structural modifications can be made to the PI backbone to modify the polymer properties, such as insertion of flexible linkages on the main chain, 9-13 use of noncoplanar 14 or asymmetric monomers [15][16][17][18][19] and incorporation of pendant groups in the polymer backbone, [20][21][22][23][24][25][26][27][28][29] with results including lower interchain interactions or a reduced polymer chain stiffness. Depending on the type and amount of structural modifications, melting temperatures can be lowered and solubility improved, resulting in processable materials.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8] Significant synthetic efforts in the area of high-performance polymers have been focused on improving the processability and solubility of PIs through the design and synthesis of new monomers. Various structural modifications can be made to the PI backbone to modify the polymer properties, such as insertion of flexible linkages on the main chain, 9-13 use of noncoplanar 14 or asymmetric monomers [15][16][17][18][19] and incorporation of pendant groups in the polymer backbone, [20][21][22][23][24][25][26][27][28][29] with results including lower interchain interactions or a reduced polymer chain stiffness. Depending on the type and amount of structural modifications, melting temperatures can be lowered and solubility improved, resulting in processable materials.…”
Section: Introductionmentioning
confidence: 99%
“…To understand the electronic structure of conjugated polymers it is essential to establish the relative positions of the characteristic electronic energy levels such as the highest occupied molecular orbital (HOMO or п level), the lowest unoccupied molecular orbital (LUMO or п), and the associated energy parameters [25,26]. The oxidation peaks in cyclic voltammograms probably correspond to the oxidation of hydroxyl groups to form phenoxy radicals.…”
Section: Electrochemical and Conductivity Propertiesmentioning
confidence: 99%
“…Thus, it is clear that various structural changes should be made in the poly(azomethine ester)'s chain to obtain better solubility and its application in various fields [9][10][11][12][13][14][15]. Some of the reported methods to improve the processability of conjugated poly(azomethine)s are by incorporation of unsymmetrical or symmetrical substitutions in the main-chain aromatic benzene rings with flexible alkyl or alkoxy side chains and reversible Lewis acidbase complexation [16][17][18][19]. Moreover, it has been already found that introduction of groups with sp 3 -hybridized atoms (-CR 2 -), ether linkage, and pendant phenyl groups can improve the solubility of polyesters [20][21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%